Effect of Transient Nicotine Load Shock on the Performance of Pseudomonas sp. HF-1 Bioaugmented Sequencing Batch Reactors - Dong-sheng Shen; Li-jia Wang; Hong-zhen He; Mei-zhen Wang (Journal of Chemistry)
Bioaugmentation with degrading bacteria can improve the treatment of nicotine-containing tobacco industrial wastewater effectively. However, the transient and extremely high feeding of pollutants may compromise the effectiveness of the bioaugmented reactors. The effect of transient nicotine shock loads on the performance of Pseudomonas sp. HF-1 bioaugmented SBRs were studied. The results showed that, under 500–2500 mg/L of transient nicotine shocks, all the reactors still could realize 100% of nicotine degradation in 4 days of recovery, while the key nicotine degradation enzyme HSP hydroxylase increased in expression. Though the dramatic increase of activities of ROS, MDA, SOD, and CAT suggested that transient nicotine shock loads could induce oxidative stress on microorganisms in activated sludge, a decrease to control level demonstrated that most of the microorganisms could resist 500–1500 mg/L of transient nicotine shock under the protection from strain HF-1. After 8 cycles of recovery, high ROS level and low TOC removal in high transient shock reactors implied that 2000–2500 mg/L of transient nicotine shock was out of its recovery of strain HF-1 bioaugmented system. This study enriched our understanding on highly efficient nicotine-degrading strain bioaugmented system, which would be beneficial to tobacco waste or wastewater treatment in engineering.